2017
DOI: 10.18287/jbpe17.03.020302
|View full text |Cite
|
Sign up to set email alerts
|

Study of glycerol diffusion in skin and myocardium ex vivo under the conditions of developing alloxan-induced diabetes

Abstract: Diabetes mellitus is one of widespread diseases, the development of which impairs the functioning of organism vital organs. The study of the processes that occur in tissues under diabetic conditions facilitates the development of diabetes diagnostics and treatment methods, as well as the prognosis of its complications. The paper reports a comparative study of glycerol diffusion in skin and myocardium of rats ex vivo in the normal condition and the conditions of alloxan-induced diabetes. The glycerol diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…15 The determination of the diffusion coefficients of OCAs and water that are characteristic to these mechanisms is highly important. Some OCAs that have been studied are glucose, 12,16 glycerol, 11,17 dimethyl sulfoxide, mannitol, propylene glycol, and x-ray contrast, such as Trazograph ™ and Omnipaque ™ . 14,18 Such studies have demonstrated a significant decrease in tissue scattering properties and an increase in tissue depth and image contrast when using imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…15 The determination of the diffusion coefficients of OCAs and water that are characteristic to these mechanisms is highly important. Some OCAs that have been studied are glucose, 12,16 glycerol, 11,17 dimethyl sulfoxide, mannitol, propylene glycol, and x-ray contrast, such as Trazograph ™ and Omnipaque ™ . 14,18 Such studies have demonstrated a significant decrease in tissue scattering properties and an increase in tissue depth and image contrast when using imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments the thickness of the treated mouse skin samples increase systematically by 5μm (Table 4), which can be explained by the decrease of the transverse dimension [47], since the weight of the treated samples has been decreased as a result of water loss and overall tissue sample shrinkage ( Table 3). The sample thickness increase did not depend on the glycerol concentration because the saturation was observed already at 30% of glycerol concentration during 5 min treatment [48].…”
Section: Registered Parameters # / Glycerol Solutionmentioning
confidence: 60%
“…In our experiments some increase of thickness of the treated rat kidney and cornea samples in diabetic and non-diabetic cases have been observed (Table 6), that can be explained by the tissue sample transverse shrinkage [26,47], since the weight of the treated samples has been decreased as a result of water loss. Figure 7 presents kinetics of the transmitted signal of the rat diabetic and non-diabetic kidney and cornea tissues treated with glycerol (70%) at the maximum of THz pulse.…”
Section: Glycerol Dehydration Of Kidney and Cornea Samples Studied Bymentioning
confidence: 93%
“…To prove the concept, kinetics of tissue permeability for selected OCAs can be studied by providing measurements of temporal collimated transmittance for tissue samples from different organs in the process of their OC. 163,177 Such comparative investigations were performed for ex vivo skin and myocardium samples of Winstar white outbred male rats using 70% glycerol solution as an OCA and the multichannel fiber-optic spectrometer USB4000-Vis-NIR (Ocean Optics, USA) operating in the spectral range of 500 to 900 nm as a measuring system. Animals were divided into the control and diabetic groups.…”
Section: Efficacy Of Optical Clearing Agents and Diffusion Coefficientmentioning
confidence: 99%